2006
DOI: 10.1097/01.bpo.0000188997.13803.25
|View full text |Cite
|
Sign up to set email alerts
|

Hand Trauma in Shop Class

Abstract: The environment and equipment used in shop class are potential sources of serious injury. There has been little published to date on injuries sustained in shop class, with no reports examining injuries to the hand. The authors report a case series collected from a health records database at a pediatric and hand surgery referral center. Fifteen patients who sustained injuries to their wrist or hand in shop class were identified. Sixty percent of the injuries were caused by table saws. Eighty percent required tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…All of the patients were male with a mean age of 16 years (range: 12–18). 6 Sixty percent of the injuries were caused by table saws, resulting in 2 index finger amputations, 1 index and long finger amputation, and lacerations and/or abrasions of various degrees of severity. The outcome of treatment was assessed at an average of 22 weeks (range: 3–66) following injury and revealed sensory and range of motion deficits in patients who had tendon, nerve, or artery repair and sensitivity in patients treated with revision amputation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the patients were male with a mean age of 16 years (range: 12–18). 6 Sixty percent of the injuries were caused by table saws, resulting in 2 index finger amputations, 1 index and long finger amputation, and lacerations and/or abrasions of various degrees of severity. The outcome of treatment was assessed at an average of 22 weeks (range: 3–66) following injury and revealed sensory and range of motion deficits in patients who had tendon, nerve, or artery repair and sensitivity in patients treated with revision amputation.…”
Section: Resultsmentioning
confidence: 99%
“…The outcome of treatment was assessed at an average of 22 weeks (range: 3–66) following injury and revealed sensory and range of motion deficits in patients who had tendon, nerve, or artery repair and sensitivity in patients treated with revision amputation. 6 These two studies indicated that shop class mishaps, while rare, frequently result in serious injury with lifelong consequences. Improper equipment use is often cited as the cause of injury meaning that traditional safety measures may not be effective in preventing injury in this population.…”
Section: Resultsmentioning
confidence: 99%
“…3 In 1 series, 60% of hand injuries in shop class were caused by table saws, and 80% required treatment by a hand surgeon. 4 Unfortunately, 67% of the cases were serious injuries, including tendon lacerations, neurovascular damage, or amputations. The majority of these patients had persistent, lifelong functional deficits at final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The former was likely due to teenagers participating in shop class, beginning occupations that may require power tool use, or simply using a power tool without proper supervision or education. 4,22 Young children are highly inquisitive and less fearful, potentially leading to their increased rate of injury. Males were far more likely to suffer from a traumatic amputation requiring hospital admission than females, especially with increasing age, a trend seen in most publications describing amputation in both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these injuries are to fingers and are the result of a diverse array of causes including fireworks, slammed doors, exercise bicycles, farm equipment, and shop class. [4][5][6]9,11,12,22,24,25,27,28 Replantation and revascularization can be successful in this patient population compared with adults as described in several case series. 1,3,7,26,30,35 The incidence, temporal trends, and patient characteristics of upper extremity traumatic amputations in children are largely unknown.…”
Section: Introductionmentioning
confidence: 99%